Upaya Meningatkan Akhlak Siswa Tingkat Sekolah Dasar - Ardiansyah Ardiansyah; Riflin Riflin; Melna Melna; Marlin Saputri Gunawan; La Ode Muhammad Fazrin (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Morals have a great influence on individuals and on a nation. Moral teachings as exemplified by Rasulullah SAW. In everyday life. The method used is to provide material in the form of morals, the pillars of Islam and the pillars of faith through infocus and conducting questions and answers. The location of the service was carried out at SD N 4 Wameo school (Class 4), the implementation lasted for three days, the PKM team became teachers and companions for the children in teaching and learning activities. The class consists of 24 students, the material that the service team brings to students is writing, reading, memorizing and listening to the stories of the Prophet. The average age of students is 10-11 years. The results obtained by students were 40% able to memorize, 70% able to read, 85% able/enthusiastic in listening to the stories of the Prophet.